Genome-wide analysis of G-quadruplexes in herpesvirus genomes - Biswas, Banhi (BMC Genomics, 2016)
BACKGROUND: G-quadruplexes are increasingly recognized as regulatory elements in human, animal, bacterial and plant genomes. The presence and function of G-quadruplexes are not well studied among herpesviruses; in particular, there are no systematic genome-wide analysis of these important secondary structures in herpesvirus genomes. RESULTS: We performed genome-wide analysis of putative quadruplex sequences (PQS) in human herpesviruses. We found unusually high PQS densities among human herpesviruses. PQS are enriched in the repeat regions and regulatory regions of human herpesviruses. Interestingly, PQS densities are higher in regulatory regions of immediate early genes compared to early and late genes in most herpesviruses. In addition, the majority of genes functionally conserved across human herpesviruses contain one or more PQS within the regulatory regions. We also describe the existence of unique intramolecular PQS repeats or repetitive G-quadruplex motifs in herpesviruses. Functional studies confirm a role for G-quadruplexes in regulating the gene expression of human herpesviruses. CONCLUSION: The pervasiveness of PQS, their enrichment and conservation at specific genomic locations suggest that these structural entities may represent a novel class of functional elements in herpesviruses. Our findings provide the necessary framework for studies on the biological role of G-quadruplexes in herpesviruses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12864-016-3282-1) contains supplementary material, which is available to authorized users.